The Problem of Availability of Learning Facilities in Achieving the Success of Islamic Religious Education - Zahro, Siti Fatimatus; Nasikhin, Nasikhin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research aims to analyze the problem of facility availability in achieving successful PAI learning objectives. This research uses qualitative methods and a narrative inquiry approach where data is collected through discussions and interviews. The data collected was analyzed using the Miles and Huberman model through reduction, display, and verification stages. The findings from this research will examine the problem of facility availability in achieving PAI learning objectives. For this reason, in this article, we will present what needs to be discussed regarding the problem of the availability of facilities in achieving the success of PAI learning objectives. The first is the role of learning facilities in supporting PAI learning objectives, the second is overcoming the constraints of limited facilities in the PAI learning process, and the third is overcoming the physical limitations of PAI learning facilities. The problem of the availability of learning facilities is one obstacle that can hinder achieving Islamic Religious Education (PAI) learning objectives. Limited or inadequate facilities, such as narrow classrooms, limited multimedia equipment, or libraries with minimal collections, can affect the effectiveness of PAI learning. The unavailability of adequate facilities can reduce students' interest and motivation in understanding and deepening PAI material, hinder interaction between teachers and students, and reduce the overall quality of learning. Therefore, increasing the availability of quality learning facilities is an important step to achieving PAI learning goals.